On the Origins of the Preface to the Second Volume of Dmitry Merezhkovsky’s Book L. Tolstoy and Dostoevsky - Elena A. Andrushchenko (Studia Litterarum)
The article analyzes the origins of the Preface to the second volume, Religion, of Dmitry Merezhkovsky’s book L. Tolstoy and Dostoevsky (1900–1902). The first publication of the book in Mir iskusstva ended with a Conclusion. When preparing a separate publication of his work (1902), Merezhkovsky published the Conclusion of Religion as a Preface without changing the original text. He used the revised text of the Conclusion for a paper entitled “Leo Tolstoy and the Russian Church” (1903). The paper includes the key points of the talk; it is an almost exact copy of the Preface to the second and third editions of the book (1903, 1909), as well as to both editions of the author’s complete works (Vol. VIII, 1912; Vol. XI, 1914). The article attempts to show the evolution of the author’s original design, explain the motives that encouraged Merezhkovsky to publish the text, reconstruct the context of the heated arguments about his book as well as his reasons to give a talk “Fathers and children of Russian liberalism” (1901).